Factors Influence Foreign Tourist’s Decision to Select A Hostel in Bangkok - Kaewkiriya, Boonnida; Buchain, Rungathit (Journal of Thai Hospitality and Tourism, 2020)
This study aims to explore personal and behavioral factors as well as marketing factors that influence foreign tourists’ decision to select a hostel in Bangkok. The study applied a quantitative approach, using a questionnaire as the method for data collection. The population sample in the study consisted of 400 foreign tourists who stayed at a hostel in Bangkok. The results reveal that the majority of the participating foreign tourists are European males at the age between 25-35 years old, who hold a bachelor’s degree, work as an employee in a private company and earn between 1,501-2,000 USD per month. The most common purpose of the travel to Thailand amongst these foreign tourists is for a leisure trip/relaxation, with the most preferred hostel characteristics being a private room en suite. The most common reason for choosing to stay at a hostel is a combination of low prices and friendly services. The foreign tourists involve only themselves when making a hostel selection decision, most often stay in a hostel during summer, and most often make a reservation on a website or via the internet. Most of these foreign tourists stay in a hostel for 2 days. The results also show that marketing factors that are most important for the participating foreign tourists when selecting a hostel are related to the services provided by the hostel staff. Most of the foreign tourists prefer a standard hostel. In conclusion, factors that influence foreign tourists’ decision to select a hostel in Bangkok include age, education level, hostel characteristics, personal reasoning for choosing a hostel over other accommodation types, and marketing factors including accommodation and service factors, price factors, factors associated with service-providing processes, and physical factors.